2003
DOI: 10.1017/s0022112003005032
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a screeching rectangular jet: a stereoscopic particle image velocimetry study

Abstract: The unsteady velocity field generated by an underexpanded jet has been investigated using stereoscopic particle image velocimetry (PIV). A 4:1 aspect ratio converging–diverging rectangular nozzle designed to operate at a fully expanded condition of $M=1.44$ was used. The nozzle was operated at off-design conditions to generate imperfectly expanded jets with intense screech tones. Phase-locked PIV measurements show the spatial and temporal evolution of the three-dimensional jet with high fidelity. In addition t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 22 publications
6
46
1
Order By: Relevance
“…The instabilities grown during the first pairing appear to be further amplified by the second pairing, due to the larger axial and radial velocity fluctuations induced by the preceding vortex ("1"). In the present case, one observes a tilting up to 30 of the trailing vortex ("2") while moving closer to vortex "1." Temporal fluctuations at a half the frequency (St ¼ 0.16) are observed, which result in further amplification of the pulsating motion.…”
Section: Three-dimensional Regime Of Circular Jetsupporting
confidence: 46%
See 3 more Smart Citations
“…The instabilities grown during the first pairing appear to be further amplified by the second pairing, due to the larger axial and radial velocity fluctuations induced by the preceding vortex ("1"). In the present case, one observes a tilting up to 30 of the trailing vortex ("2") while moving closer to vortex "1." Temporal fluctuations at a half the frequency (St ¼ 0.16) are observed, which result in further amplification of the pulsating motion.…”
Section: Three-dimensional Regime Of Circular Jetsupporting
confidence: 46%
“…Zaman and Raman 29 placed tabs at the exit of turbulent circular jet reporting a marked loss of azimuthal coherence and the generation of pairs of streamwise vortices, which contribute to the increase of the lateral spreading of the jet along the direction orthogonal to the plane of the tabs. Streamwise structures are also formed in rectangular jets, as shown by the phased-locked stereo PIV measurements by Alkislar et al 30 More recently, El Hassan and Meslem 2 studied the entrainment of circular and daisy-shaped orifice jets at Re ¼ 3600 using time-resolved stereo PIV and snapshot POD analysis. They concluded that the daisy-shaped orifice jet undergoes earlier transition due to the generation of streamwise vortices, with a significant enhancement of the entrainment process.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…They are also a favorable choice to achieve thrust vectoring control. In the past several decades, many studies have been carried out to reveal the fundamental characteristics of supersonic jets from various rectangular nozzles [1][2][3][4][5][6]. For instance, in his study regarding the impact of rectangular nozzle aspect ratios on jet noise, Bridges [1] revealed that rectangular nozzles were able to reduce jet noise to a great degree than axisymmetric nozzles.…”
Section: Introductionmentioning
confidence: 99%